Properties and performance of polypropylene fibered high-strength concrete with an improved composite binders - Amran, Mugahed; Lesovik, Valery; Tolstoy, Aleksandr; Fediuk, Roman; Rusinov, Roman; Rusinova, Nadezhda; Qader, Diyar N.; Mohammed, Kachalla; Rashid, Raizal S.m. (Elsevier BV, 2022)
Fibrous high-strength concrete by means of natural and technogenic raw materials is in demand for sustainable construction. The scientific novelty of this study lies in the expansion of the range of applied natural raw materials locally available for polymineral binders, instead of using manufactured or rare materials. This research aimed to improve the performance and properties of high-strength concrete with an improved composite binder and polypropylene fiber. The task was achieved by using a powdered mineral modifier, the introduction of which will make it possible to effectively control the processes of synthesis of hydration products during the hardening of the cement composite. The study of the characteristics of the feedstock included: energy density, particle size distribution, and specific surface area. A comprehensive study of the obtained materials properties included: X-ray diffraction analysis, scanning electron microscopy, standard consistency, setting time, compressive and flexural strength, elastic modulus, structural quality factor, water retention capacity, adhesion strength, water resistance, abrasion resistance, thermal conductivity. It is proposed to use an energy measure that allows ranking raw materials to produce building materials. Optimization of the micro and macro level structural component using local raw materials, makes it possible to attain a compressive strength of materials by about 80 MPa, a flexural capacity and an elastic modulus of 15.2 MPa and 78.4 GPa respectively. The developed mortar and polypropylene fiber-reinforced concrete is a reliable and durable material that retains its specified performance characteristics over time without destruction under operating conditions. Water holding capacity observed was 89.5% which is 1.54 times higher than that of unmodified composition, adhesion strength to the base 0.90 (80% higher). Additionally the observed structural quality factor was 0.36 (4 times higher), water resistance under pressure 0.8 MPa (0.2 MPa for unmodified composition), abrasion was 0.70 g/cm2 (59% lower), thermal conductivity coefficient was 1.29 W/(m·ºС) (56% lower). Comprehensive results evidenced of using high-strength materials for a wide range of structures, including load-bearing, enclosing, road, hydraulic.